Factors Affecting Cuff Extrusion of Tunneled Hemodialysis Catheters. Issue 2 (May 2022) - Parvulescu, Flavius; Oliver, Matthew J.; Reyna, Myrtha E.; Pugash, Robyn; David, Elizabeth
Purpose: To identify patient and procedural factors associated with extrusion of the Dacron cuff from the subcutaneous tunnel of tunneled hemodialysis catheters (THDCs). Materials and methods: Single center 5-year retrospective analysis of 625 catheters in 293 adult patients. Patient data included age, gender, body mass index (BMI), and common comorbidities. Procedural details included type of procedure (new insertion vs. exchange), operator seniority, side of insertion, catheter model and presence of catheter wings skin-sutures. Complications were reported as cumulative risk over time and Cox proportional hazards model was used to evaluate risk factors for cuff extrusion (CE). Results: Median patient follow-up was 503 days (188, 913 catheter-days) and median catheter survival 163 days. CE occurred in 23.8% of catheters, at a rate of 0.79 per 1, 000 catheter-days and a median time of 64 days. It was more common than infection (14.6%) and inadequate flow (15.5%). The 1-month and 12-month risk of CE was 5.9% and 21.3% respectively. A first episode of CE was a strong predictor of future CE episodes. The only patient factor that affected the risk of CE was BMI (Hazard Ratio 2.36 for obese patients). Procedural factors that affected the risk of CE, adjusted for BMI, were catheter model, type of procedure (lower risk for new insertions) and catheter wings skin-sutures; the latter reduced the 30-day CE risk by 76% without increasing catheter-related infections. Conclusion: Cuff extrusion is common in long-term THDCs. The risk increases with obesity, history of previous cuff extrusion, certain catheter models and absence of wing-sutures.